(untitled) (Semiárida, 2020)
The trial was carried out to study dry matter yield of 2 barley (Hordeum vulgare L.) cultivars, and your seasonal distribution. A methodology of sequential cut (with weekly frequency) was utilized, working with 5 clipping series with 3 repetitions each. Bordenave Ranquelina showed a better initial growth rateo After the middle may, growth rates (Tp, kg DM/ha/day) of Uñaiché INTA was higher (P < 0,05) than B. Ranquelina. The highest Tp (30.28 kg DM/ha/day) corresponded to Uñaiché INTA, and was shown at middle mayo The growth equations of each cultivar was determined. Dry matter yields (2,237.4 and 1,983.6 kg/ha, for Uñaiché INTA and B. Ranquelina, respectively) were signlficatively differents (P < 0,01).